2021
DOI: 10.1111/imm.13338
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in ocular mucosal tolerance: Lessons learned from gut and respiratory tract immunity

Abstract: Summary The ocular surface is the part of the visual system directly exposed to the environment, and it comprises the cornea, the first refractive tissue layer and its surrounding structures. The ocular surface has evolved to keep the cornea smooth and wet, a prerequisite for proper sight, and also protected. To this aim, the ocular surface is a bona fide mucosal niche with an immune system capable of fighting against dangerous pathogens. However, due to the potential harmful effects of uncontrolled inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 158 publications
(216 reference statements)
1
6
0
1
Order By: Relevance
“…Therefore, elderly patients are prone to refractory dry mouth, dry eyes, irritant cough, and other symptoms. [24] In addition, we found that arthritis, Raynaud, and parotid enlargement were more common in the AopSS patients, which was consistent with other studies. [8,10] These clinical features are similar to lung characteristics (NSIP/OP), suggesting inflammation is prominent in AopSS patients.…”
Section: Eopsssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, elderly patients are prone to refractory dry mouth, dry eyes, irritant cough, and other symptoms. [24] In addition, we found that arthritis, Raynaud, and parotid enlargement were more common in the AopSS patients, which was consistent with other studies. [8,10] These clinical features are similar to lung characteristics (NSIP/OP), suggesting inflammation is prominent in AopSS patients.…”
Section: Eopsssupporting
confidence: 92%
“…[23] In addition, tolerance of trachea mucous membrane to external antigen stimulation weakens during aging. [24] Therefore, age might be an independent risk factor for ILD and more attention is needed for lung disorders in elderly pSS patients.…”
Section: Discussionmentioning
confidence: 99%
“…When modern eye drugs with preservatives are used concurrently with chronic allergic reactions in the ocular surface in elderly patients, the condition may be misdiagnosed as dry eye [ 54 ]. Patients with dry eyes are more likely to be sensitive and experience symptoms similar to allergic rhinoconjunctivitis [ 55 ]. The strong correlation between the naturally occurring flora of the gut and the occurrence of respiratory diseases is comparable to conjunctival approval.…”
Section: Reviewmentioning
confidence: 99%
“…Booth et al compared the T cell responsiveness of elderly people with younger individuals (>60 vs. <60 years of age) and reported that in tissue resident memory T cells (T RM ) in ileum tissue, cellular characteristics, function, and number are affected by aging [ 83 ]. Furthermore, as reviewed by Galletti et al [ 84 ], in aging mice, the induction of tolerance as well as the humoral response to the oral administration of ovalbumin are decreased. Our own data suggested that oral immunizations induced both allergen-specific IgG1 and IgG2a in aged animals, while adult animals preferentially developed IgG1.…”
Section: The Aged Intestine: Alteration Of Intestinal Barriermentioning
confidence: 99%